Study of the Interaction of Dextran and Enoxaparin on Haemostasis in Humans - Matthiasson, Stefan E; Lindblad, Bengt; Mätzsch, Thomas; Molin, Jarl; Qvarfordt, Peter; Bergqvist, David (Thrombosis and Haemostasis, 1994)
The effect on haemostatic variables by dextran 70, enoxaparin and their combinations, given in doses of 500 ml i.v. and 40 mg s.c. respectively, was studied in a randomised cross-over fashion in twelve healthy male volunteers. Antifactor-IIa activity, antifactor-Xa activity, APTT, factor VIII, vWF, bleeding time and blood counts were analysed over a 24-h period. Dextran alone did not affect antifactor-IIa activity and antifactor-Xa activity. No difference in antifactor-IIa and antifactor-Xa activity was found for Amax, tmax, AUC0-8 h and AUC0-24 h in the groups treated with enoxaparin or the combination of enoxaparin and dextran. Only minor changes in APTT were observed without statistical significance between the treatment groups. Factor VIII did not change significantly in the three treatment groups. However, vWF was significantly reduced in the dextran and the dextran/enoxaparin group (p = 0.046 and 0.01 respectively) but no difference was found between the two groups. Bleeding time was not significantly increased four hours after administration of the test substances and no difference was found between the individual treatment groups. Our findings indicate that dextran can be combined with enoxaparin, when used in thromboprophylactic doses, without increased risk for bleeding.